Needs Analysis of Teaching Materials for Learning Discourse Analysis - Yusrina, Yusrina; Tang, Muhammad Rapi; Saud, Syukur (Proceeding of International Conference on Language Pedagogy (ICOLP), 2021)
Teaching materials are one of the important aspects that determine the effectiveness of learning. In learning discourse analysis, students are expected to have critical thinking skills, but this is not achieved because the teaching materials used are not in accordance with the needs of students. The purpose of this study was to analyze the needs of teaching materials to students. This research was conducted by quantitative descriptive method. Research data were collected using a questionnaire given to 30 students. The data from the questionnaires were then studied using quantitative descriptive analysis methods. Based on the results of the study obtained data that many teaching materials are not in accordance with the learning objectives that have been formulated in the lesson plan. The pattern of preparation and content of teaching materials used so far does not provide a stimulus for students to develop critical thinking skills. The results showed that students not only needed teaching materials that contained material as the object of discourse analysis studies, but also needed material on concepts and strategies in critical thinking.